Evaluation of an identification method for the SARS-CoV-2 Delta variant based on the amplification-refractory mutation system - Zhang, Qin; Qiao, Runjie; Niu, Jiaojiao; Xiong, Xia; Wang, Nan; Zhang, Ruixian; Luo, Sha; Guo, Yuwan; Liu, Zhonghua; Peng, Li; Zhang, Shaoduo; Tan, Guolei; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
The Delta variant of SARS-CoV-2 dominated the COVID-19 pandemic due to its high viral replication capacity and immune evasion, causing massive outbreaks of cases, hospitalizations, and deaths. Currently, virus strain identification is performed mainly by sequencing. However, the high requirements for equipment and operators as well as its high cost have limited its application in underdeveloped regions. Therefore, an urgent need exists for a rapid and economical method for virus strain identification. Here, we applied ARMS-PCR for the detection of novel coronavirus variants. The obtained results showed that the ARMS-PCR assay is fast, sensitive, and specific, and could be used for high-throughput detection. In a set of double-blind trials, tests of 262 samples revealed that our method was able to accurately identify the Delta variant with high sensitivity and specificity. It is worth adding that the three sites we targeted could also be used for the identification of other strains in the B.1.617 lineage. In conclusion, our proposed assay has high sensitivity and specificity, and is suitable for global promotion, especially in underdeveloped regions.